2012
DOI: 10.1007/s10162-012-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Adaptation of the Human Angular Vestibulo-Ocular Reflex

Abstract: A recent study showed that the angular vestibuloocular reflex (VOR) can be better adaptively increased using an incremental retinal image velocity error signal compared with a conventional constant large velocity-gain demand (×2). This finding has important implications for vestibular rehabilitation that seeks to improve the VOR response after injury. However, a large portion of vestibular patients have unilateral vestibular hypofunction, and training that raises their VOR response during rotations to both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 35 publications
2
43
3
Order By: Relevance
“…During active head impulses, the two patients who quickly learned the adaptation training had significant adaptation toward the ipsilesional adapting side (+43.2% and +39.2%) and minimal adaptation toward the nonadapting side (j14.3% and j5.6%). These increases were greater than those seen in previous studies on bilateral and unilateral incremental adaptation training in UVH subjects (9) and normal subjects (10), respectively. For the other two patients, there was evidence of unilateral short-term adaptation, particularly in patient B1, whose VOR gain increased from 0.08 to 0.38 during passive head impulses toward the adapting side.…”
Section: Figcontrasting
confidence: 73%
See 2 more Smart Citations
“…During active head impulses, the two patients who quickly learned the adaptation training had significant adaptation toward the ipsilesional adapting side (+43.2% and +39.2%) and minimal adaptation toward the nonadapting side (j14.3% and j5.6%). These increases were greater than those seen in previous studies on bilateral and unilateral incremental adaptation training in UVH subjects (9) and normal subjects (10), respectively. For the other two patients, there was evidence of unilateral short-term adaptation, particularly in patient B1, whose VOR gain increased from 0.08 to 0.38 during passive head impulses toward the adapting side.…”
Section: Figcontrasting
confidence: 73%
“…We did not use the incremental (initial gain = 1.1 demand driven to a final target gain = 2) adaptation training technique, which for bilateral adaptation has been shown to more effectively increase the VOR gain compared with Â2 ''all-at-once'' adaptation training (9). Instead, in this study, we used a continual Â1.5 (''all-at-once'') training, which for unilateral adaptation seems to be just as effective as the incremental adaptation training (10). This preliminary result suggests that the 0.1 increment in target gain between training epochs during incremental adaptation training (9,10) may be conservative.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Majorly, those subjects use an optical correction with only about 2% having insufficient correction (31). Optical corrections are known to magnify (plus lenses) or miniaturize (minus lenses) the visual surrounding and adapt the VOR gain direction and frequency specific (32)(33)(34)(35)(36). In case of higher age we have to consider adaptive effects of magnifying optical corrections, which increase the VOR gain.…”
Section: What Causes the ''Refixating Saccades''?mentioning
confidence: 98%
“…Migliaccio and Schubert [23] suggest that with as little as 15 minutes of tutoring, unilateral incremental VOR adaptation can be stimulated in normal subjects. Their experiments showed that during active head impulses, VOR gain in the adapting direction was increased by -22% and by -11% during passive ones.…”
Section: Discussionmentioning
confidence: 99%